Heavy-metal-induced ethylene production in Arabidopsis thaliana - Arteca, Richard N (Journal of plant physiology, 2007)
Different plant parts varied in copper sulfate (CuSO(4)) and cadmium sulfate (CdSO(4))-induced ethylene production, inflorescences showed the greatest induction, while all other plant parts tested produced significantly less. Leaf age had a dramatic effect on CuSO(4) and CdSO(4)-induced ethylene production with the youngest leaves showing the greatest stimulation and as the age of the leaf increased there was a reduction in their ability to produce ethylene. However, there was no significant difference in CuSO(4), CdSO(4) and wound-induced ethylene production when whole rosettes were taken from plants that were 7, 14 or 21-day-old. The highest amount of CuSO(4) and CdSO(4)-induced ethylene production was produced in the root tip with regions below this producing less. CuSO(4) and CdSO(4)-induced ethylene production was also greatest from the tip of the inflorescence to 2cm below the tip and from this point down there was a reduction in ethylene production. When inflorescence stalks or leaves were treated with CuSO(4) or CdSO(4) over a range of concentrations from 0 to 800microM, there was an increase in ethylene production starting at 50microM with increasingly greater responses up to 400microM. There was no further increase at the 800microM CuSO(4) concentration; however, there was a slight decline with 800microM CdSO(4). Inflorescence stalks or leaves treated with either 400microM CuSO(4) or CdSO(4) exhibited a dramatic increase in ethylene production 2h following treatment initiation and remained high over a 24-h period with a decline in ethylene production after this time in inflorescence stalks but not the leaves. It was found that light caused a dramatic decrease in CuSO(4), CdSO(4) and wound-induced ethylene production in both inflorescence stalks and leaves. When inflorescence stalks or leaves were treated at 43 degrees C, there was a dramatic effect on CuSO(4), CdSO(4) and wound-induced ethylene production in each